Japan at the crossroads : conflict and compromise after Anpo - Kapur, Nick, 1980- (Harvard University Press, 2018)
Japan at the Crossroads explains how massive protests in Japan against the US-Japan alliance in 1960 produced enduring transformations in Japanese politics, society, and culture, as well as in US-Japan relations and the Cold War international system. The protests were the largest popular protests in Japan's modern history, lasting more than a year and reaching a violent climax in June 1960, when thousands of radical activists stormed the National Legislature, precipitating a battle with police and yakuza thugs which injured thousands. Although the protests ultimately failed to prevent passage of the Security Treaty, which remains in force to this day, they did shock the nation and the world, leading to the cancelation of a greatly anticipated visit to Japan by US president Eisenhower, the resignation of Japanese prime minister Kishi Nobusuke, and ultimately, the reformulation of US-Japan diplomacy and Japanese political and social relations.--